Two year old adults: Clinical Navigation through Precocious Puberty - Syal, Simran; George Mathew, Prakash; Goel, Anil Kumar (Indian Journal of Child Health, 2025)
Precocious puberty is defined as the onset of puberty below the age of eight years in girls and nine years in boys. It is etiologically classified as central and peripheral depending on the source of hormone production. We present a couple of cases of two year old males who presented with increased penile length, pubic hair and height spurt along with testicular volume enlargement. Thus, a clinical diagnosis of isosexual central precocious puberty was made. Central precocious puberty was confirmed by pubertal levels of gonadotropins. MRI brain showed the presence of hypothalamic hamartoma. Both the children were started on Gonadotropin releasing hormone (GnRH) analogs. We use these cases to highlight the paramount importance of a thorough clinical examination including genital examination in all children and emphasize on physical measurement of testicular volume by accurately using an orchidometer as an important step to decide the further line of evaluation and management.